2021
DOI: 10.1038/s41598-021-00263-0
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusions increase the risk for venous thromboembolism events following total joint arthroplasty

Abstract: The association between blood transfusions and thromboembolic events (VTE) following total joint arthroplasty (TJA) remains debatable. Using contemporary institutional data, this study aimed to determine whether blood transfusions increase the risk of VTE following primary and revision TJA. This was a single institution, retrospective cohort study. The clinical records of all patients (n = 34,824) undergoing primary and revision TJA between 2009 and 2020 were reviewed. Demographic variables, co-morbidities, ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Acuña et al [ 22 ] found that the receipt of a postoperative transfusion was relevant to an increased risk of VTE in 333, 463 patients with total knee arthroplasty. Furthermore, another single-center retrospective cohort study also confirmed that the risk of VTE following total joint arthroplasty increased by approximately three-fold when blood transfusions were prescribed [ 7 ]. Patients often receive acute transfusion during the perioperative period.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Acuña et al [ 22 ] found that the receipt of a postoperative transfusion was relevant to an increased risk of VTE in 333, 463 patients with total knee arthroplasty. Furthermore, another single-center retrospective cohort study also confirmed that the risk of VTE following total joint arthroplasty increased by approximately three-fold when blood transfusions were prescribed [ 7 ]. Patients often receive acute transfusion during the perioperative period.…”
Section: Discussionmentioning
confidence: 93%
“…However, as both TH and PSH are associated with hypercoagulability and inflammatory response. One might speculate that the observed excess VTE risk could be related to increased blood viscosity and inflammation [ 7 , 35 , 36 ]. Thus, it is likely to speculate that a biological interaction between TH and PSH on the risk of VTE could be mediated via procoagulant changes arising from two sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all hip fracture patients over the study period who received TXA, the median dose was 2 g of intravenous (IV) TXA administered intraoperatively in 2 divided doses on incision and closure. Control variables were determined a priori 12 on the basis of previous work demonstrating associations with the outcomes of interest [13][14][15][16][17] . The following patient variables were included: age, sex, body mass index (BMI), Charlson Comorbidity Index, ASA class, and preoperative tobacco use.…”
Section: Methodsmentioning
confidence: 99%
“…Most observational studies investigating VTE ignored the role of allogeneic blood transfusion as a causal factor. Few studies found in cancer and after surgery that blood transfusions were dosedependently associated with VTE [74][75][76]. One study in 1070 patients undergoing cardiac surgery found a dose-dependent association with transfusion of blood products and VTE [77].…”
Section: Allogeneic Transfusion and Thrombosismentioning
confidence: 99%